A critical review of optimizing pollutant removal from refinery wastewater using ozone and nanocatalyst-assisted bubble column reactors - Safiaa M. Mohammed; Khalid A. Sukkar; Ali Abdul Rahman Al-Ezzi; Amjed R. Qarahgouli (Desalination and Water Treatment)
The treatment of petroleum refinery wastewater remains a critical challenge due to the complex mixture of toxic and persistent contaminants such as hydrocarbons, phenolic compounds, nitrogenous substances, and heavy metals. Among emerging technologies, the integration of nanoparticle catalysts within packed ozonation bubble column reactors has emerged as a promising strategy for enhancing the degradation of both organic and inorganic pollutants. Although ozonation and nanocatalyst-assisted bubble column reactors (BCRs) research has attracted growing attention, there is currently a lack of a systematic summary to bridge the gap between lab-scale studies and pilot-scale applications. Therefore, this review presents a comprehensive analysis of recent advances in ozonation technologies, reactor design, and the strategic use of nanocatalysts to enhance ozonation efficiency, to clarify current challenges and propose future research directions. The innovative contribution of this review lies in its systematic summary of research on BCRs combined with catalytic ozonation to address the limitations of conventional treatment systems and provide theoretical guidance for transitioning these systems from the laboratory scale to practical applications. It was found that the catalytic ozonation with BCRs offers unique advantages, including high oxidation potential, rapid pollutant breakdown, and minimal formation of harmful intermediates. The catalytic ozonation process achieved pollutant removal of more than 80 % for phenol and COD. Catalytic ozonation with BCRs achieved 100 % removal efficiency for phenol as well as partial removal of heavy metals and other pollutants. On the other hand, an in-depth review was needed, focusing on the key roles of reactor configuration, catalyst selection, and operational parameters to optimize pollutant removal. This review outlines future directions for scaling up ozonation technologies and improving the sustainability and cost-effectiveness of refinery wastewater treatment. This study contributes valuable insights and frameworks into the design and implementation of next-generation catalytic ozonation systems tailored for petroleum industry effluents.